PENGARUH MODEL PEMBELAJARAN BRAIN WRITING TERHADAP KETERAMPILAN MENULIS NASKAH DRAMA SISWA KELAS VIII SMP SWASTA SABILINA TAHUN AJARAN 2023/2024 - Putri, Putri; Naelofaria, Salmah (Asosiasi dosen IDEBAHASA KEPRI, 2024)
This research aims to determine the influence of the Brain Writing Learning Model on the Drama Script Writing Skills of Class VIII Students at Sabilina Private Middle School. The population in this study was all class VIII, totaling 192 students. The sample consisted of 60 students divided into 2 classes, namely the control class with 30 students and the experimental class with 30 students. The research uses the Brain Writing learning model for drama script writing skills. This research is a type of quantitative research with experimental methods. The research design used was true group post-test. The data analysis techniques used are analysis requirements tests, normality tests, and hypothesis tests. The results of research in writing drama scripts using conventional methods are in the fair category with an average score of 67 and the results of research using the Brain Writing learning model are in the good category with an average score of 83. Based on the results of the normality test, namely the control class 0.111661 < 0.161 and experimental class 0.15383 < 0.161. Based on hypothesis testing, it is obtained that tcount > ttable is 6.0836 > 1.70113 so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. The results of this research indicate that there is quite a significant influence from the use of the Brain Writing Learning Model on the Drama Script Writing Skills of Class VIII Students at Sabilina Private Middle School for the 2023/2024 Academic Year.